Application of novel genetic methods for studies of unsaturated fatty acid synthesis in Pseudomonas aeruginosa - Choi, Kyoung-hee, author; Schweizer, Herbert P., advisor; Carlson, Jonathan O., committee member; Belisle, John T., committee member; Pilon, Marinus, committee member (Colorado State University. Libraries, 2006)
As with most bacteria, the development of genetic tools for Pseudomonas aeruginosa and related bacteria has not kept up with the pace of sequencing and high-throughput post-genomic technologies, e.g. microarrays. In the course of this dissertation, new genetic tools were developed that accelerate post-genomic studies. The utility of these tools was then tested for studies on the mechanism and regulation of unsaturated fatty acid (UFA) biosynthesis in P. aeruginosa. The tools developed here include a broad-host-range transposon Tn7-based site-specific gene integration system, a rapid and efficient bacterial transformation method, and a rapid gene replacement method. Traditional methods used for chromosomal insertion of exogenous DNA rely mostly on either species-specific methods (e.g., phage integration systems) or on randomly integrating transposons. To overcome these and other limitations of traditional methods, a Tn7-based integration system was developed. This transposon inserts site- and orientation-specifically downstream of the essential glmS gene in P. aeruginosa and other bacteria. Since insertions occur at a naturally-evolved, neutral intergenic chromosomal site so that bacterial fitness is not affected. Mini-Tn7 vectors were developed for single-copy genetic complementation, gene and protein fusion analyses, reporter gene tagging and gene expression studies. Because of its broad-host-range, the mini-Tn7 system was shown to be applicable in many other gram-negative organisms including Burkholderia spp. and Yersinia pestis. A rapid transformation method was developed in support of the mini-Tn7 system. This method is generally applicable for delivery of genetic elements such as replicative and non-replicative plasmids, suicide delivery vectors, gene replacement vectors and chromosomal fragments containing selection markers. In the absence of a reliable transduction method, the latter procedure is especially useful for strain construction because it allows transfer of mutations tagged with an antibiotic selection marker between different strains. To facilitate high-throughput mutant construction, a combination of rapid transformation and Gateway recombinational cloning was implemented to greatly improve and accelerate a relatively tedious traditional gene replacement procedure. UFAs play an essential role in cellular physiology by maintaining proper membrane fluidity in response to changes in various environmental conditions such as temperature, oxygen, toxic compounds, growth, osmotic pressure, and hydrostatic pressure. Generally, microbial UFAs are synthesized via two different pathways: 1) enzymes encoded by the fabA, fabB and other genes which belong to the type II fatty acid biosynthetic pathways. This pathway is found in many bacteria, including Escherichia coli and Streptococcus pneumoniae', and 2) by aerobic desaturation of saturated fatty acids (SFAs) by an inducible desaturase activity. This pathway is found in gram-positive bacteria (e.g., Bacillus subtilis), mycobacteria and Saccharomyces cerevisiae. These organisms typically lack FabA and FabB homologs. In this study, we showed that UFA synthesis in P. aeruginosa is unique in that this bacterium uses both of the pathways mentioned above. Even though two pathways exist for UFA production and the FabAB pathway is not required for aerobic growth, the FabA and FabB proteins are indispensable for anaerobic growth because of the oxygen-dependency of the enzymes of the aerobic pathway. There are two distinct desaturase genes in P. aeruginosa that are desA and desB encoding acyl-lipid desaturase and acyl-CoA desaturase, respectively. During aerobic growth, DesA, but not DesB, is capable of complementing the UFAauxotrophy of fabAB mutants by introducing the double bond into the fatty acyl chain of phospholipids. In contrast, DesB acts on the CoA-esterified form of exogenous long chain fatty acids. The desB gene forms an operon with desC, encoding a putative oxidoreductase which is thought to be involved in providing electrons from the electron transport chain for the DesB-catalyzed reaction. Microarray and RT-PCR analyses demonstrated that the desBC operon is under DesT repressor control. Under anaerobic conditions, UFAs are derived from de novo fatty acid synthesis, and FabA and FabB are essential players in this process. Previous studies showed that the P. aeruginosa fabA and fabB genes form an operon whose expression was up-regulated in biofilm-grown cells and repressed by exogenous fatty acids, especially oleic acid. Since the molecular mechanism underlying these observations remained a mystery, the newly developed genetic tools were employed to study regulation of fabAB operon expression. These studies revealed that transcription of the fabAB operon is complex. While it is most likely co-transcribed with the upstream PA1612-PA1611 operon, it is also transcribed by a second promoter which is either located in the PA1611-fabA intergenic region or somewhere within the PA1612-PA1611 operon. The PA1611-fabA intergenic region contains a 30 bp regulatory element which is highly conserved and present only in Pseudomonas spp. Deletion of this sequence greatly reduced fabA expression and abolished repression by exogenous UFAs, strongly suggesting a role as an important regulatory DNA sequence. However, repeated genetic and biochemical attempts failed to identify fabAB regulatory protein(s). Gene deletion experiments demonstrated that none of the targeted regulatory genes, including all of the transcriptional regulators of the GntR family to which the E. coli fabA and fabB activator belongs, encodes an activator of fabAB expression. While the combination of random mariner transposon mutagenesis and gene fusion technology revealed several genes, including rpoN, desA, anr and several of unknown function, that exhibited an effect on fabAB expression, follow up studies revealed only an indirect and in most cases moderate role of these genes in regulation of fabAB expression. Biochemical attempts involved DNA affinity chromatography with 30 bp concatamer or PA1611-fabA intergenic region substrates, but all of these attempts failed to identify specific DNA binding proteins. In summary, the data reveal that transcriptional regulation of fabAB operon expression is complex, involving several promoters, a conserved DNA regulatory element and probably several unidentified regulatory factors. The inability to identify a specific DNA binding protein by powerful genetic and biochemical methods suggests that fabAB operon expression may not simply be governed by protein-DNA interactions, but rather by a more complex regulatory mechanism(s), e.g. involvement of a riboregulatory element.
Keywords: microbiology